2019
DOI: 10.1155/2019/9206948
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Levels of Nitric Oxide Oxidative Metabolites with Acute Stroke in Patients Presenting to the Emergency Department of a Low-Middle Income Country

Abstract: Introduction. Acute stroke incites an inflammatory reaction in the brain’s microvasculature, activating formation of nitric oxide oxidative metabolites, nitrate and nitrite (NOx, collectively), measurable in plasma. Our objectives were to investigate plasma NOx in patients with acute stroke presenting to the Emergency Department (ED) and to determine if it could (i) differentiate between ischemic and hemorrhagic stroke; (ii) predict clinical outcomes. Methods. A cross-sectional study was conducted in the ED of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In previous studies, the circulating levels of NOx have been determined in ischemic [25,55] and hemorrhagic [56] stroke. In those studies, an initial decrease on NOx was observed compared to healthy volunteers, which progressively increased through the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the circulating levels of NOx have been determined in ischemic [25,55] and hemorrhagic [56] stroke. In those studies, an initial decrease on NOx was observed compared to healthy volunteers, which progressively increased through the hospital stay.…”
Section: Discussionmentioning
confidence: 99%